2019
DOI: 10.3390/ijms21010160
|View full text |Cite
|
Sign up to set email alerts
|

Photocycle Dynamics of the Archaerhodopsin 3 Based Fluorescent Voltage Sensor QuasAr1

Abstract: The retinal photocycle dynamics of the fluorescent voltage sensor QuasAr1 (Archaerhodopsin 3 P60S-T80S-D95H-D106H-F161V mutant from Halorubrum sodomense) in pH 8 Tris buffer was studied. The samples were photoexcited to the first absorption band of the protonated retinal Schiff base (PRSB) Ret_580 (absorption maximum at λmax ≈ 580 nm), and the retinal Schiff base photoisomerization and protonation state changes were followed by absorption spectra recordings during light exposure and after light exposure. Ret_5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…As the starting template, we chose Archon1 (Piatkevich et al, 2018), which is an evolved version of Archaerhodopsin 3 that has been demonstrated for in vivo voltage imaging in mice (Fan et al, 2020;Piatkevich et al, 2019) and zebrafish larvae (Böhm et al, 2021). Since the voltage-sensing mechanism of rhodopsin-derived GEVIs is not fully understood (Maclaurin et al, 2013;Penzkofer et al, 2019Penzkofer et al, , 2021, it is difficult to adopt a structure-guided approach to design the mutant library.…”
Section: Directed Evolution Of Arch-derived Gevismentioning
confidence: 99%
“…As the starting template, we chose Archon1 (Piatkevich et al, 2018), which is an evolved version of Archaerhodopsin 3 that has been demonstrated for in vivo voltage imaging in mice (Fan et al, 2020;Piatkevich et al, 2019) and zebrafish larvae (Böhm et al, 2021). Since the voltage-sensing mechanism of rhodopsin-derived GEVIs is not fully understood (Maclaurin et al, 2013;Penzkofer et al, 2019Penzkofer et al, , 2021, it is difficult to adopt a structure-guided approach to design the mutant library.…”
Section: Directed Evolution Of Arch-derived Gevismentioning
confidence: 99%
“…This area is the largest in terms of the number of related publications and includes 91 articles, namely [ 1 , 2 , 3 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 ,…”
Section: Articles On the Various Directionsmentioning
confidence: 99%
“…The last one seems to be the most detailed, and it is precisely this that we will try to implement in the course of our narrative. As it should be expected, a priori, most of the publications in this direction are devoted to organic compounds, and primarily organic molecules; these include, with varying degrees of correctness, publications [ 1 , 2 , 3 , 102 , 103 , 104 , 106 , 108 , 112 , 117 , 118 , 119 , 121 , 124 , 127 , 128 , 130 , 131 , 132 , 133 , 135 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 146 , 147 , 148 , 151 , 153 , 154 , 156 , 157 , 164 , 165 , 166 , 168 , 171 , 172 , 174 , 176 , 178 , 180 , 183 , 185 , 186 ]. Much less space is occupied by the works related to polymeric (in fact, to a high molecular weight) compounds [ 113 , …”
Section: Articles On the Various Directionsmentioning
confidence: 99%
“…Archaerhodopsin 3 (Arch) from Halorubrum sodomense exhibits measurable voltage dependence of fluorescence efficiency and was studied as voltage indicator [ 17 , 28 , 29 ]. For improvement of fluorescence efficiency and voltage sensitivity, variants of Arch have been synthesized by gene technical methods [ 28 , 29 , 30 , 31 , 32 , 35 , 37 , 43 , 44 , 45 , 46 ]. Arch and Arch D95N were used for optical recording of action potentials in cultured rat hippocampal neurons [ 28 ] and in HEK-293 cells [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The absorption and emission spectroscopic behavior and thermal stability of QuasAr1 was investigated in [ 44 ]. Its photocycle dynamics was studied in [ 45 ]. QuasAr3 (=QuasAr2 K171R) and paQuasAr3 (=QuasAr3 V59A) were applied to in vivo recording of supra- and subthreshold voltage dynamics from multiple neurons in mouse hippocampus [ 31 ].…”
Section: Introductionmentioning
confidence: 99%